STRATEGI PEMERINTAH KABUPATEN TANGERANG DALAM MEMPEROLEH PENGHARGAAN PENGELOLAAN SP4N-LAPOR! TERBAIK NASIONAL - Faizal Mubarak Keliobas; Nida Handayani (PT. Hasba Edukasi Mandiri, 2025)
Managing public service complaints is a crucial part of realizing responsive and transparent governance. Tangerang Regency is one of the regions that has received national awards for its SP4N-LAPOR! management, making it interesting to examine its implementation strategy. This study aims to analyze the Tangerang Regency Government's strategy in managing SP4N-LAPOR! to achieve national recognition, using descriptive qualitative methods with Wheelen and Hunger's (1998) strategic implementation theory, which includes three indicators: program development, budgeting, and procedures. The results indicate that the program development strategy was implemented consistently, with 100% report completion and high public participation. From a budgetary perspective, significant funding allocations from the regional budget (APBD) and central government support through training demonstrate a commitment to strengthening institutional capacity. Meanwhile, from a procedural perspective, Tangerang Regency has a comprehensive standard operating procedure (SOP) and a robust coordination system, although challenges remain in terms of socialization and inclusiveness of application use. Overall, the SP4N-LAPOR! implementation strategy is considered effective in improving the quality of public services, although improvements are still needed to reach all levels of society equally.